Effects of acidity on pollen germination and tube length of Malus sylvestris Miller cv. Golden and Pyrus communis L. - Topdemir, Aykut; Gür, Nazmi (My University, 2011)
The aim of this study is to investigate the effects of acidity on in vitro pollen germination and tube length of Mains sylvestris Miller cv. Golden and Pyrus communis L plants. Pollens from flowers of Ma/us sylvestris Miller cv Golden and Pyrus communis L have been exposed at the effect of artificial acid solutions, at pH values from 6.2 to 2.8 at 0.2 intervals. Brawbaker Kwack medium was used for pollen germination. According to the results obtained, germination rate and pollen tube length for each plant at least has been affected at pH 6.2. Pollen germination and tube length decreased high rate with increasing acidity. The decrease of in these rates were calculated 99.44 % for Mains sylvestris Miller cv. Golden pollen germination and 99.68 % for tube length; 96.23 % for Pyrus communis L pollen germination and 96.75% for tube length at pH 2.8.
Bildiri - Yayımlanmamış
Keywords: Acidity; Pollen germination; Tube length; Mallus Sylvestris Miller cv. Golden; Pyrus Communis L.